Reproducción y densidad de la liebre cola-negra (Lepus californicus) en relación a factores ambientales, en la Reserva de la Biosfera Mapimí, Desierto Chihuahuense. - Portales-Betancourt, Gloria L.; Hernández Laundré, Lucina; Laundré, John W.; Cervantes, Fernando (THERYA, 2012)
The knowledge on the reproduction of wildlife species is necessary for an appropriate conservation or management program. Currently, very few studies have been carried out on the reproductive biology and demography of Lepus californicus in the Chihuahuan Desert; and the role of environmental factors in these processes. Also, the information on their population densities and the factors that determine their growth or decrease are of great relevance for to know the patterns in the reproduction of the species. The objective of this study was to describe the reproductive patterns of L. californicus in relation to temperature, precipitation, evaporation and photoperiod, and the relative abundance of the species at the Mapimí Biosphere Reserve (RBM). Testicular weight was positively correlated with photoperiod (R = 0.80, P = 0.01). Ovary weight was correlate with photoperiod (R = 0.92, P = 0.0001), average environmental temperature (R = 0.71, P= 0.037) and precipitation (R = 0.82, P = 0.015). Results indicate that photoperiod is the main factor that promotes the beginning of the reproductive cycle, although females may need multiple factors to respond to the high annual variability in the production of plants. Different response between males and females to environmental stimuli may be due to different reproductive strategies. For females, reproductive cost is greater that for males, they respond to a complex series of environmental cues, as a strategy to maximize its reproductive success.